Analisis Mekanisme dan Tingkat Keparahan Potensi Interaksi Obat Pada Pasien Diabetes Melitus Rawat Inap: Analysis of the Mechanism and Severity of Potential Drug Interactions in Hospitalized Diabetes Mellitus Patients - Teguh Wibowo; Julia Totong; Imam Syafi’i (Journal of Nursing Education and Practice, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder that frequently requires combination therapy, which may increase the risk of drug interactions. These interactions can influence the safety and effectiveness of pharmacological treatment, especially in hospitalized patients who often experience multiple comorbid conditions and receive various medications simultaneously.Objective: This study aimed to analyze the potential drug interactions in hospitalized patients with diabetes mellitus.Methods: This study applied a descriptive analytic approach with a retrospective design using medical record data. The analysis focused on identifying potential drug interactions based on prescribed medications. The potential interactions were evaluated using a drug interaction database to determine their mechanisms and severity levels.Results: The findings indicate that hospitalized patients with diabetes mellitus commonly receive multiple medications due to the presence of comorbid diseases. The use of combination therapy increases the possibility of potential drug interactions. Most interactions identified were related to pharmacodynamic and pharmacokinetic mechanisms. In terms of severity, moderate interactions were more frequently observed compared with other categories. These interactions mainly occurred among antidiabetic agents and medications used to treat accompanying conditions.Conclusion: Potential drug interactions among hospitalized patients with diabetes mellitus are relatively common due to the complexity of therapy and the presence of comorbidities. Careful monitoring of medication therapy and collaboration among healthcare professionals are important to ensure safe and effective treatment and to minimize the risk of adverse drug interactions.